Local Escapes: Decoding the Staycationer Mindset Across Generations - Olfa Ammar (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2026)
Background: Staycation, a tourism trend emerging in response to changing lifestyles, global crises, and increasing sustainability awareness, is transforming traditional vacation habits. Although vacations close to home were once perceived as less exciting, they have become an attractive alternative for many, but specific, travelers. Purpose: This study analyses consumers’ attitudes, motivations, and preferences toward staycations as a vacation alternative, highlighting both their appeal and the skepticism surrounding them across generations. Method: A qualitative research design was adopted, based on 20 in-depth semi-structured interviews conducted with participants recruited through purposive sampling. Diversity was ensured across age, gender, and travel habits, with participants categorized into Generation Z and Millennials. Guided by a lifestyle (AIO) perspective, the data were analyzed using thematic analysis supported by QDA Miner, following an iterative coding process to identify recurring themes and cross-generational patterns. Findings: The qualitative data analysis revealed four prominent market segments, each characterized by unique preferences, expectations, and travel behaviors. The results demonstrate that while staycations are valued for their psychological benefits, convenience, affordability, and environmental consciousness, perceptions of excitement and novelty vary across segments. Conclusions: The present research demonstrates that staycation has evolved from a proximity-based travel option into a differentiated form of tourism consumption. The identification of four lifestyle-based segments reveals marked generational differences, where Generation Z tends to associate staycation with stimulation and novelty, whereas Millennials emphasize psychological detachment and quality time. These results demonstrate that staycation adoption is shaped by lifestyle orientations and psychological considerations rather than by spatial or economic constraints. Research implication: This study contributes theoretically by integrating the Benefits Theory of Leisure Wellbeing and Psychological Capital theories to extend staycation beyond crisis-driven tourism and to position it as a lifestyle-based approach for sustaining wellbeing. From a managerial perspective, this research provides actionable insights for tourism marketers to develop tailored staycation packages targeting the identified consumer segments.